Peran Mahasiswa Fakultas Hukum Dalam Mendorong Dan Meningkatkan Kesadaran Hukum Hak Asasi Manusia Terhadap Pelajar SMAN 3 Di Kabupaten Kuningan - Anthon Fathanudien (Pusmedia Group Indonesia, 2025)
This community service activity is a manifestation of the implementation of the Tri Dharma of Higher Education which focuses on improving students' understanding of legal developments in Indonesia. The background of this activity stems from the problem of low legal awareness among students, especially in understanding the law which is often ignored in social interactions in the school environment. This condition causes the still rampant behavior of bullying, discrimination, drugs, brawls, and other violations of individual rights. To address this problem, the implementing team conducted a socialization activity at SMAN 3 Kuningan Regency which was attended by 40 students using a normative legal lecture approach, interactive discussions, and case studies. This method is designed so that participants not only understand the theory, but also are able to identify and analyze problems that occur in the school environment in the context of everyday life in the educational environment. The results of the activity showed an increase in student understanding of the law, awareness of the importance of law enforcement in schools, and the emergence of a critical attitude towards actions that have the potential to violate individual rights. In addition, the discussion also emphasized the strategic role of teachers and the guidance and counseling department in building a school culture that respects human values. Overall, this community service activity provides a positive contribution to efforts to strengthen legal awareness and develop the character of students who uphold an understanding of law in Indonesia, while also expanding the role of higher education in building a just and civilized society.